Sodium ferrous fluorophosphate / N-CNT composite positive electrode active material and its preparation and application in sodium ion battery

By using sodium ferrous fluorine phosphate/N-CNT composite material in the positive electrode material of sodium ion battery, the high preparation cost and electrochemical performance of existing materials are solved by preforming the iron phosphate phase and ammoniacal calcining with CNT. The best problem is to achieve efficient preparation of materials and excellent electrochemical properties.

CN115275126BActive Publication Date: 2025-02-18HUNAN NABANG NEW ENERGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202110483080.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-04-30
Publication Date
2025-02-18
Estimated Expiration
2041-04-30

AI Technical Summary

Technical Problem

The existing preparation methods for the positive electrode materials of sodium ion batteries require expensive raw materials, and the crystalline phase structure and morphological uniformity of the material are not ideal, and the electrochemical performance needs to be improved.

Method used

Using sodium ferrous fluorophosphate/N-CNT composite positive electrode active material, iron and phosphorus are formed into iron phosphate phases in advance, and ammonia-calcined with carbon nanotubes (CNT), followed by sodium and fluorination roasting, to control The crystalline phase structure and morphology of the material.

Benefits of technology

Improves the electrochemical properties of the material, including capacity, magnification and cycle stability, reduces production costs, and achieves high purity and good morphology of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0003049173650000011
    Figure HDA0003049173650000011
  • Figure HDA0003049173650000012
    Figure HDA0003049173650000012
  • Figure HDA0003049173650000021
    Figure HDA0003049173650000021
Patent Text Reader

Abstract

The present invention belongs to the field of electrode material technology, and relates to a sodium ferrous fluorophosphate / N-CNT composite positive active material, including N-CNT, and sodium ferrous fluorophosphate composited on N-CNT. In addition, the present invention further relates to a method for preparing the material, which mixes iron phosphate and carbon nanotubes and then performs ammoniation roasting to obtain an iron phosphate / N-CNT intermediate; then the iron phosphate / N-CNT intermediate, a fluorine source and a sodium source are mixed, and then roasting treatment is performed to obtain the sodium ferrous fluorophosphate / N-CNT composite positive active material. The technical solution of the present invention, pre-ammoniation roasting of iron and phosphorus with iron phosphate phases is carried on the N-CNT structure, and then subsequent sodiumization and fluorination roasting are involved, so that the sodium ferrous fluorophosphate crystal phase structure can be controlled, the unit cell size can be controlled, the material morphology can be improved, and the ion and electronic conduction network construction can be effectively constructed, thereby effectively improving the capacity, rate and cycle stability of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical field:

[0001] The present invention relates to the field of batteries, and in particular to the technical field of positive electrode materials for sodium ion batteries. Background technology:

[0002] Lithium-ion batteries have rapidly occupied the portable electronic product market and are constantly penetrating into the field of electric vehicles due to their advantages such as high energy density, high stability, and long life. However, the reserves of lithium resources in the earth's crust are low and the geographical distribution is uneven, which has caused the price of lithium to continue to rise during the large-scale promotion and application of lithium-ion batteries, resulting in high prices for lithium-ion batteries. Therefore, the application of lithium-ion batteries in the field of large-scale power storage is limited. Lithium and sodium belong to the same main group and have good chemical reserves, but the radius of the sodium element is larger than that of the lithium element. Many materials and material construction theories suitable for lithium-ion batteries are difficult to apply in the field of sodium-ion batteries, and it is difficult to obtain technical effects similar to those of lithium-ion batteries. This is the main reason why lithium-ion batteries have been widely used while sodium-ion batteries have not been widely commercialized.

[0003] The research on positive electrode materials for Na-ion batteries has evolved from layered oxide positive electrode materials to tunnel structure oxide materials. The final direction has shifted to the research of olivine structured polyanion positive electrode materials. These compounds have high thermal stability due to the strong covalent bonds of oxygen atoms in the polyanion polyhedrons, and because they have multidimensional ion migration channels, they have good ion embedding / de-embedding stability, making them suitable choices for Na-ion battery positive electrode materials.

[0004] Fluorophosphoric acid system transition metal materials have a lattice structure different from the phosphoric acid system, providing a two-dimensional channel for ion conduction, which is conducive to the improvement of discharge stability and capacity. Na2FePO4F has a high theoretical capacity (124mAh·g -1 ) and a stable charge and discharge platform (3.0V), and a stable structure, making it a promising sodium-ion battery cathode material.

[0005] At present, sodium ferrous fluorophosphate is usually obtained by directly sintering iron source (ferrous acetate, ferrous oxalate, ferric nitrate), phosphoric acid, sodium source, fluorine source and carbon source raw materials; this method requires relatively expensive raw materials. In addition, the crystal structure and morphology uniformity of the synthesized material are not ideal, and the electrochemical performance needs to be further improved. Summary of the invention:

[0006] In view of the problems of the prior art, the first purpose of the present invention is to provide a sodium ferrous fluorophosphate / N-CNT composite positive electrode active material, aiming to obtain a new material that is conducive to the insertion and deinsertion of sodium ions and improves the electrochemical performance of sodium ion batteries.

[0007] The second object of the present invention is to provide a method for preparing a sodium ferrous fluorophosphate / N-CNT composite positive electrode active material, and in particular to a method for preparing the material using materials recycled from waste.

[0008] The third object of the present invention is to provide an application of sodium ferrous fluorophosphate / N-CNT composite positive electrode active material in sodium ion batteries.

[0009] The fourth object of the present invention is to provide a sodium ion battery containing the sodium ferrous fluorophosphate / N-CNT composite positive electrode active material.

[0010] A sodium ferrous fluorophosphate / N-CNT composite positive electrode active material, comprising N-CNT and sodium ferrous fluorophosphate composited on the N-CNT;

[0011] The N-CNT is an N-hybridized (doped) carbon nanotube.

[0012] The present invention innovatively loads sodium ferrous fluorophosphate on the surface of N-CNT. The material has a good sodium ion and electron conduction network and can effectively improve the electrochemical performance of the material in a sodium ion battery.

[0013] The material described in the present invention, the synergistic combination of material and morphology is the key to improving the electrochemical performance of the material.

[0014] In the present invention, the diameter of the CNT is preferably 5-15 nm; the length is preferably 0.5-2 μm.

[0015] Preferably, the N content in N-CNT is 1 to 5 atm %.

[0016] The present invention also provides a method for preparing the sodium ferrous fluorophosphate / N-CNT composite positive electrode active material, comprising the following steps:

[0017] Step (1):

[0018] The iron phosphate and carbon nanotubes are mixed and then subjected to ammoniation and calcination to obtain an iron phosphate / N-CNT intermediate;

[0019] Step (2):

[0020] The ferric phosphate / N-CNT intermediate, the fluorine source and the sodium source are mixed, and then calcined to obtain the sodium ferrous fluorophosphate / N-CNT composite positive electrode active material.

[0021] Different from the conventional solid phase and sol-gel preparation methods, the technical solution of the present invention pre-ammoniation and calcination of iron and phosphorus in the form of iron phosphate phase to load them on the N-CNT structure, and then participate in subsequent sodium and fluorination calcination. In this way, the crystal phase structure of sodium ferrous fluorophosphate and the unit cell size can be controlled, the material morphology can be improved, and the ion and electron conduction network can be effectively constructed, thereby effectively improving the capacity, rate and cycle stability of the material.

[0022] The present invention has found that the use of an iron phosphate intermediate phase and the simultaneous ammoniation and calcination of CNTs are the key to improving material properties and electrochemical performance.

[0023] In the present invention, the ferric phosphate is obtained by pre-reacting a trivalent iron source and a phosphate source;

[0024] Preferably, the iron source is Fe 3+ The water-soluble salt is preferably at least one of ferric chloride, ferric sulfate, ferric nitrate, ferric acetate and ferric citrate;

[0025] The phosphorus source is PO4 3- The water-soluble acid or salt is preferably at least one of phosphoric acid, sodium dihydrogen phosphate, ammonium dihydrogen phosphate, disodium hydrogen phosphate, and diammonium hydrogen phosphate.

[0026] The iron source and the phosphorus source are mixed according to a stoichiometric ratio.

[0027] In another embodiment of the same inventive concept of the present invention, the iron phosphate is obtained by a recycling process of waste materials containing phosphorus or iron;

[0028] Preferably, the titanium dioxide byproduct ferrous sulfate is obtained by recycling;

[0029] The preferred recovery steps are:

[0030] The ferrous sulfate produced as a byproduct of titanium dioxide is oxidized and then pre-reacted with a phosphorus source to obtain an iron phosphate intermediate.

[0031] The oxidizing agent for the oxidation treatment is an oxidizing agent capable of converting Fe 2+ Oxidized to Fe 3+ The substance may be, for example, at least one of hydrogen peroxide, sodium peroxide, and potassium peroxide.

[0032] In the present invention, the oxidation product and the phosphorus source are pre-reacted to obtain an iron phosphate phase intermediate. Preferably, the phosphorus source is at least one of phosphoric acid, sodium dihydrogen phosphate, ammonium dihydrogen phosphate, disodium hydrogen phosphate, and diammonium hydrogen phosphate;

[0033] Preferably, the pH of the pre-reaction process is 1.5-3.

[0034] For example, the preferred steps of using titanium dioxide byproduct ferrous sulfate to obtain an iron phosphate intermediate are: dissolving the titanium dioxide byproduct ferrous sulfate in deionized water, placing it in a reactor, adding an oxidant to oxidize ferrous ions to trivalent ferrous ions, heating (50-80°C) and stirring to obtain solution A; slowly adding phosphoric acid to solution A, then dripping ammonia water to adjust the pH value to 1.5-3, obtaining a slurry with white floccules, performing solid-liquid separation on the slurry, washing, drying, and grinding to obtain an iron phosphate precursor. The drying treatment temperature is 60-120°C, and the drying treatment time is 12-48h.

[0035] In the present invention, iron and phosphorus are innovatively formed into iron phosphate, and it is further innovatively ammoniation-sintered with CNTs. This helps to further improve the physical, crystal and morphology of the obtained material, helps to construct an ion and electron conduction network, and helps to improve the electrochemical properties of the material.

[0036] Preferably, the mass ratio of iron phosphate to CNT is 9.5-8.5:0.5-1.5; more preferably, it is 9-9.5:0.5-1.

[0037] In the present invention, the iron phosphate and CNT can be compounded in a liquid phase, and then subjected to solid-liquid separation, drying and ammoniation calcination.

[0038] In the present invention, the ammoniation calcination process is carried out in an atmosphere containing ammonia.

[0039] For example, the ammonia-containing atmosphere may be ammonia, or a mixture of ammonia and nitrogen, or a mixture of ammonia and argon.

[0040] Preferably, the temperature of the ammoniation calcination process is 350-500°C; more preferably, 350-400°C.

[0041] Preferably, the heating rate of the ammoniation calcination process is 1-5°C / min.

[0042] Preferably, the ammoniation calcination time is 2 to 6 hours.

[0043] In the present invention, an iron phosphate / N-CNT intermediate is innovatively used as a precursor, and further sintered with a sodium source and a fluorine source, thereby improving the crystal phase and structure of the material and contributing to improving the electrochemical properties of the material.

[0044] Preferably, the sodium source is a component capable of providing the Na element, preferably at least one of sodium carbonate, sodium bicarbonate, sodium acetate, sodium dihydrogen phosphate and disodium hydrogen phosphate;

[0045] Preferably, the fluorine source is a component capable of providing a fluorine source, preferably at least one of sodium fluoride, ammonium fluoride or hydrogen fluoride;

[0046] Preferably, the iron phosphate / N-CNT intermediate (calculated by moles of iron phosphate), the sodium source, and the fluorine source are mixed in a molar ratio of iron phosphate:F:Na of 1-1.2:1-1.3:1-1.1.

[0047] In the present invention, the iron phosphate / N-CNT intermediate, the sodium source, and the fluorine source can be mixed in a liquid phase manner, for example, by wet ball milling.

[0048] When wet ball milling is used, the ball milling medium of the material is, for example, ethanol and / or acetone. The ball milling speed is 200-700 rpm. The ball milling time is preferably 6-12 hours.

[0049] Preferably, in step (2), the calcination process is carried out under a protective atmosphere;

[0050] Preferably, the protective atmosphere is one or more of nitrogen, argon, nitrogen-hydrogen mixed gas, and argon-hydrogen mixed gas;

[0051] Preferably, the temperature of the calcination process is 500-750°C; more preferably 600-700°C;

[0052] Preferably, the calcination time is 6 to 12 hours;

[0053] Preferably, the heating rate during the calcination process is 1-10° C. / min.

[0054] Considering the dual factors of cost and material performance, the preferred embodiment of the present invention is: using titanium dioxide byproduct to prepare sodium ferrous fluorophosphate / N-CNT, the steps are as follows:

[0055] (1) dissolving ferrous sulfate, a byproduct of titanium dioxide, in deionized water, placing the solution in a reaction kettle, adding an oxidant to oxidize ferrous ions into ferric ions, heating the solution (50 to 80° C.) and stirring the solution to obtain a solution A;

[0056] (2) slowly adding phosphoric acid to the solution A in step (1), and then dropping ammonia water to adjust the pH value to 1.5-3 to obtain a slurry with white floccules, and subjecting the slurry to solid-liquid separation, washing, drying, and grinding to obtain an iron phosphate precursor;

[0057] (3) ultrasonically dispersing the carbon nanotubes in deionized water, adding the iron phosphate precursor obtained in step (2) after the carbon nanotubes are evenly dispersed, grinding the mixture into powder after drying, and sintering the mixture in an ammonia atmosphere to obtain a modified iron phosphate / N-CNT precursor powder;

[0058] (4) The iron phosphate / N-CNT precursor powder, fluorine source and sodium source prepared in step (3) are placed in a ball mill according to a molar ratio of iron phosphate: F: Na of 1 to 1.2:1 to 1.3:1, and after being fully ground by ball milling, they are placed in a quartz crucible and calcined under a protective atmosphere to obtain a sodium ferrous fluorophosphate / N-CNT composite material.

[0059] The present invention uses ferrous sulfate, a byproduct of titanium dioxide, as a raw material to prepare an iron phosphate precursor, and modifies the precursor, and then sintering with a fluorine source and a sodium source by high-speed oscillation ball milling at high temperature to further obtain sodium ferrous fluorophosphate / N-CNT sodium positive electrode material. The source of the precursor iron phosphate of the method is low in price and green and environmentally friendly, the method has simple process steps, low cost, is suitable for large-scale synthesis, and the obtained product has uniform particle size, high purity, and good electrochemical performance.

[0060] The preferred solution of the present invention uses titanium dioxide byproduct ferrous sulfate as raw material to obtain iron phosphate, and then sintering the iron phosphate and carbon nanotubes in ammonia to obtain a modified iron phosphate / N-CNT intermediate, and then sintering with a fluorine source and a sodium source at high temperature to further obtain sodium ferrous fluorophosphate / N-CNT sodium positive electrode material. The method is characterized in that the production cost of sodium ferrous fluorophosphate is further reduced by using titanium dioxide byproduct as raw material, and the iron phosphate is modified. The final obtained sodium ferrous fluorophosphate / N-CNT has high crystallinity, small particle size, and the surface is evenly coated with a carbon nanotube conductive layer with nitrogen defects, and its electronic conductivity is improved. At the same time, the surface has more active sites, so it has excellent electrochemical properties. In addition, the synthesis process is simple and suitable for large-scale synthesis.

[0061] The present invention also provides an application of the sodium ferrous fluorophosphate / N-CNT composite positive electrode active material, which is used to prepare a sodium ion battery, preferably to prepare a positive electrode of a sodium ion battery.

[0062] The present invention also includes a sodium ion battery, which comprises the sodium ferrous fluorophosphate / N-CNT composite positive electrode active material.

[0063] A preferred sodium ion battery, wherein the positive electrode contains the sodium ferrous fluorophosphate / N-CNT composite positive electrode active material;

[0064] A further preferred sodium ion battery has a positive electrode material containing the sodium ferrous fluorophosphate / N-CNT composite positive electrode active material.

[0065] Beneficial Effects

[0066] (1) The present invention provides a sodium ferrous fluorophosphate / N-CNT composite positive electrode active material of a new substance and structure, and it is found that the material has good electrochemical properties;

[0067] (2) The present invention also provides a method for preparing the material, which innovatively forms an iron phosphate phase with iron and P in advance, and further cooperates with CNT ammoniation calcination and subsequent Na-F calcination, which can achieve synergy, improve the physical phase and crystal structure and purity of the prepared material, and improve the electrochemical performance of the prepared material;

[0068] (3) The present invention can use waste recycling to obtain iron phosphate, which is then subjected to ammoniation calcination with CNTs, and further subjected to subsequent sodium-fluoride calcination. This can achieve waste utilization, reduce costs, and help obtain materials with good performance.

[0069] For example, in the preferred embodiment of the present invention, ferrous sulfate, a byproduct of titanium dioxide, can be used as a raw material to prepare iron phosphate, and then the iron phosphate / N-CNT precursor powder can be obtained after modification. This method reduces the cost of material synthesis and contributes to performance improvement.

[0070] The present invention first modifies the iron phosphate precursor, then mixes it with the fluorine source and the sodium source and then sintering to obtain the sodium ferrous fluorophosphate / N-CNT composite material. The final sodium ferrous fluorophosphate / N-CNT has high crystallinity, small particle size, and a surface uniformly coated with a carbon nanotube conductive layer with nitrogen defects, and its electronic conductivity is improved. At the same time, the surface has more active sites, so it has excellent electrochemical properties. Description of the drawings:

[0071] Figure 1 XRD pattern of iron phosphate precursor

[0072] Figure 2 XRD pattern of sodium ferrous fluorophosphate

[0073] Figure 3 SEM image of sodium ferrous fluorophosphate

[0074] Figure 4 Circulation diagram of the material obtained in Example 1

[0075] Figure 5 Circulation diagram of the material obtained in Example 2

[0076] Figure 6 Circulation diagram of the material obtained in Example 3

[0077] Figure 7 Circulation diagram of the material obtained in Example 4

[0078] Figure 8 Circulation diagram of the material obtained in Example 5

[0079] Fig. 9 Circulation diagram of the material obtained in Example 6

[0080] Fig.10 Circulation diagram of the material obtained in Comparative Example 1

[0081] Fig.11 Circulation diagram of the material obtained in Comparative Example 2

[0082] Fig.12 Circulation diagram of the material obtained in Comparative Example 3

[0083] Fig.13 Circulation diagram of the material obtained in Comparative Example 4

[0084] Fig.14 The cycle diagram of the material obtained in Comparative Example 5

[0085] Fig.15 Circulation diagram of the material obtained in Comparative Example 6 Specific implementation method:

[0086] Embodiment 1:

[0087] Preparation of sodium ferrous fluorophosphate / N-CNT composite positive electrode material:

[0088] (1) 5 mmol of ferrous sulfate (Fe 2+ ) was dissolved in deionized water, put into a reactor, 8 mmol of hydrogen peroxide was added as an oxidant to oxidize ferrous ions to trivalent ferrous ions, the temperature was raised to 50°C, and the mixture was stirred at a rate of 500 rpm. Subsequently, 5 mmol of phosphoric acid (equimolar to Fe) was slowly added, and then ammonia water was added dropwise to adjust the pH value to 2 to obtain a slurry with white floccules. The slurry was subjected to solid-liquid separation, washed three times with deionized water, put into an oven at 120°C for 12 hours, and then taken out and ground to obtain an iron phosphate precursor powder;

[0089] (2) CNTs were weighed and ultrasonically dispersed in deionized water according to the mass ratio of iron phosphate to carbon nanotubes (mass ratio of 9:1), and iron phosphate was added after uniform dispersion. After stirring at 80°C for 5 h, the mixture was dried and ground into powder, and sintered at 400°C for 4 h under ammonia to obtain modified iron phosphate / N-CNT precursor powder;

[0090] (3) The modified iron phosphate / N-CNT precursor powder (calculated by the molar amount of iron phosphate) was obtained, and then added into a ball mill (with ethanol as the medium) with sodium acetate and sodium fluoride in a FePO4:Na:F molar ratio of 1:1.1:1.1, the rotation speed was adjusted to 500 rpm, and after ball milling for 8 hours, the powder was sintered at 600°C for 10 hours in an argon atmosphere to obtain a high-performance sodium ferrous fluorophosphate / N-CNT composite positive electrode material.

[0091] Embodiment 2:

[0092] Compared with Example 1, the only difference is that in step (2), the mass ratio of iron phosphate to CNT is different, which is 9.5:0.5.

[0093] Embodiment 3:

[0094] Compared with Example 1, the only difference is that in step (2), the mass ratio of iron phosphate to CNT is different, which is 8.5:1.5.

[0095] Embodiment 4:

[0096] Compared with Example 1, the only difference is that in step (2), the ammoniation sintering system is different, the sintering temperature is 350° C., and the holding time is 5 h.

[0097] Embodiment 5:

[0098] Compared with Example 1, the only difference is that in step (2), the ammoniation sintering system is different, the sintering temperature is 500° C., and the holding time is 2 h.

[0099] Embodiment 6:

[0100] Compared with Example 1, the only difference is that in step (3), the sintering system is different, the sintering temperature is 700° C., and the holding time is 8 h.

[0101] Comparative Example 1:

[0102] Compared with Example 1, the only difference is that the modification of step (2) is not carried out as required, and the iron phosphate obtained in step (1) is directly added to a ball mill (the medium is ethanol) in a molar ratio of FePO4:Na:F of 1:1.1:1.1, the rotation speed is adjusted to 500 rpm, and after ball milling for 8 hours, the sodium ferrous fluorophosphate positive electrode material is obtained after sintering at 600°C for 10 hours in an argon atmosphere.

[0103] Comparative Example 2:

[0104] Compared with Example 1, the only difference is that the amination calcination temperature in step (2) is 600°C.

[0105] Comparative Example 3:

[0106] Compared with Example 1, the only difference is that in step (2), CNT and iron phosphate are not aminated at the same time. First, CNT is aminated and calcined at 400° C. for 5 h to obtain N-CNT, and then N-CNT, iron phosphate, sodium acetate and sodium fluoride are mixed and sintered according to the mixing ratio and sintering mechanism of step (3) of Example 1 to obtain iron phosphate / N-CNT precursor powder.

[0107] Comparative Example 4:

[0108] Compared with Example 1, the only difference is that iron and phosphorus are not pre-reacted to form an iron phosphate phase; instead, ferric sulfate, ammonium phosphate, N-CNT (prepared in an ammonia atmosphere, at 400°C for 5 hours), sodium acetate and sodium fluoride are directly mixed and sintered according to the mixing ratio (Fe:P:Na:F=1:1:1.1:1.1, wherein FePO4:CNT=9:1) and sintering mechanism of step (3) of Example 1.

[0109] Comparative Example 5

[0110] Compared with Example 1, the only difference is that iron sulfate, ammonium phosphate and CNT are ball-milled and mixed (the medium is ethanol), and then a first roasting and a subsequent second roasting are performed. The process parameters are the same as Example 1.

[0111] Comparative Example 6

[0112] Compared with Example 1, the only difference is that an amorphous carbon source (glucose) is used to replace CNT, and the process parameters are the same as Example 1.

[0113] The electrical properties of the sodium ferrous fluorophosphate prepared in each embodiment and comparative example were tested:

[0114] The main steps of the test are:

[0115] (1) Using a 2032 model battery case, the positive electrode is a prepared sodium ferrous fluorophosphate electrode (the current collector is aluminum foil, active material: conductive carbon: PVDF = 7:2:1), the negative electrode is sodium metal, a fiber separator (model Whatman Grade GF / D), and the electrolyte is 1M NaClO4 (pure PC + 5% FEC) to assemble the battery;

[0116] (2) The rest time is 12 h, and a rate charging program is set, with a rate of 0.1C, a voltage range of 2.0 V-4.0 V, and 50 cycles;

[0117] (3) The theoretical specific capacity of sodium ferrous fluorophosphate is 124 mAh / g;

[0118] The test results are shown in Table 1:

[0119] First cycle capacity (mAh / g) Capacity after 50 cycles (mAh / g) Capacity retention rate (%) Example 1 118.2 114.8 97.1 Example 2 114.5 109.1 95.3 Example 3 115.2 108.5 94.2 Example 4 112.9 104.8 92.8 Example 5 110.8 104.9 94.7 Example 6 113.6 109.2 96.1 Comparative Example 1 84.5 72.2 85.4 Comparative Example 2 93.5 79.2 84.7 Comparative Example 3 85.1 73.3 86.1 Comparative Example 4 90.2 77.5 85.9 Comparative Example 5 78.2 65.5 83.8 Comparative Example 6 84.3 69.5 82.4

[0120] It can be seen that by adopting the method described in the present invention, the iron source and the phosphorus source are formed into an iron phosphate phase in advance, and then it and CNT are jointly subjected to ammoniation calcination, and further subsequent sodium-fluorination calcination, a material with good electrochemical properties can be obtained.

Claims

1. A sodium ferrous fluorophosphate / N-CNT composite positive electrode active material, characterized in that: It includes N-CNT, and sodium ferrous fluorophosphate composited on the N-CNT; The N-CNT is an N-hybridized carbon nanotube; The sodium ferrous fluorophosphate / N-CNT composite positive electrode active material is prepared by a method comprising the following steps: Step (1): The iron phosphate and carbon nanotubes are mixed and then subjected to ammoniation and calcination to obtain an iron phosphate / N-CNT intermediate; Step (2): The ferric phosphate / N-CNT intermediate, the fluorine source and the sodium source are mixed, and then calcined to obtain the sodium ferrous fluorophosphate / N-CNT composite positive electrode active material.

2. A method for preparing the sodium ferrous fluorophosphate / N-CNT composite positive electrode active material according to claim 1, characterized in that: The following steps are involved: Step (1): The iron phosphate and carbon nanotubes are mixed and then subjected to ammoniation and calcination to obtain an iron phosphate / N-CNT intermediate; Step (2): The ferric phosphate / N-CNT intermediate, the fluorine source and the sodium source are mixed, and then calcined to obtain the sodium ferrous fluorophosphate / N-CNT composite positive electrode active material.

3. The method for preparing the sodium ferrous fluorophosphate / N-CNT composite positive electrode active material according to claim 2, characterized in that: The ferric phosphate is obtained by pre-reacting a trivalent iron source and a phosphorus source.

4. The method for preparing the sodium ferrous fluorophosphate / N-CNT composite positive electrode active material according to claim 3, characterized in that: The ferric iron source is Fe 3+ water-soluble salts.

5. The method for preparing the sodium ferrous fluorophosphate / N-CNT composite positive electrode active material according to claim 4, characterized in that: The ferric iron source is at least one of ferric chloride, ferric sulfate, ferric nitrate, ferric acetate and ferric citrate.

6. The method for preparing the sodium ferrous fluorophosphate / N-CNT composite positive electrode active material according to claim 3, characterized in that: The phosphorus source is PO4 3- water-soluble acids or salts.

7. The method for preparing the sodium ferrous fluorophosphate / N-CNT composite positive electrode active material according to claim 6, characterized in that: The phosphorus source is at least one of phosphoric acid, sodium dihydrogen phosphate, ammonium dihydrogen phosphate, disodium hydrogen phosphate and diammonium hydrogen phosphate.

8. The method for preparing the sodium ferrous fluorophosphate / N-CNT composite positive electrode active material according to claim 2, characterized in that: The ferric phosphate is obtained by recycling waste materials containing phosphorus or iron.

9. The method for preparing the sodium ferrous fluorophosphate / N-CNT composite positive electrode active material according to claim 8, characterized in that: The ferric phosphate is obtained by recycling ferrous sulfate, a byproduct of titanium dioxide.

10. The method for preparing the sodium ferrous fluorophosphate / N-CNT composite positive electrode active material according to claim 9, characterized in that: The recycling steps are: The ferrous sulfate produced as a byproduct of titanium dioxide is oxidized and then pre-reacted with a phosphorus source to obtain an iron phosphate intermediate.

11. The method for preparing the sodium ferrous fluorophosphate / N-CNT composite positive electrode active material according to claim 10, characterized in that: The phosphorus source is at least one of phosphoric acid, sodium dihydrogen phosphate, ammonium dihydrogen phosphate, disodium hydrogen phosphate, and diammonium hydrogen phosphate.

12. The method for preparing the sodium ferrous fluorophosphate / N-CNT composite positive electrode active material according to claim 10, characterized in that: The pH of the pre-reaction process is 1.5~3.

13. The method for preparing the sodium ferrous fluorophosphate / N-CNT composite positive electrode active material according to claim 2, characterized in that: The mass ratio of iron phosphate to CNT is 9.5~8.5:0.5~1.

5.

14. The method for preparing the sodium ferrous fluorophosphate / N-CNT composite positive electrode active material according to claim 2, characterized in that: The ammoniating calcination process is carried out in an atmosphere containing ammonia.

15. The method for preparing the sodium ferrous fluorophosphate / N-CNT composite positive electrode active material according to claim 2, characterized in that: The temperature of the ammoniating calcination process is 350~500℃.

16. The method for preparing the sodium ferrous fluorophosphate / N-CNT composite positive electrode active material according to claim 2, characterized in that: The ammoniating calcination time is 2~6h.

17. The method for preparing the sodium ferrous fluorophosphate / N-CNT composite positive electrode active material according to claim 2, characterized in that: The sodium source is a component that can provide the Na element.

18. The method for preparing the sodium ferrous fluorophosphate / N-CNT composite positive electrode active material according to claim 17, characterized in that: The sodium source is at least one of sodium carbonate, sodium bicarbonate, sodium acetate, sodium dihydrogen phosphate and disodium hydrogen phosphate.

19. The method for preparing the sodium ferrous fluorophosphate / N-CNT composite positive electrode active material according to claim 2, characterized in that: The fluorine source is a component that can provide a fluorine source.

20. The method for preparing the sodium ferrous fluorophosphate / N-CNT composite positive electrode active material according to claim 19, characterized in that: The fluorine source is at least one of sodium fluoride, ammonium fluoride or hydrogen fluoride.

21. The method for preparing the sodium ferrous fluorophosphate / N-CNT composite positive electrode active material according to claim 2, characterized in that: The iron phosphate / N-CNT intermediate, the sodium source and the fluorine source are mixed according to the molar ratio of iron phosphate:F:Na element of 1~1.2:1~1.3:1~1.

1.

22. The method for preparing the sodium ferrous fluorophosphate / N-CNT composite positive electrode active material according to claim 2, characterized in that: In step (2), the calcination process is carried out under a protective atmosphere.

23. The method for preparing the sodium ferrous fluorophosphate / N-CNT composite positive electrode active material according to claim 22, characterized in that: The protective atmosphere is one or more of nitrogen, argon, nitrogen-hydrogen mixed gas, and argon-hydrogen mixed gas.

24. The method for preparing the sodium ferrous fluorophosphate / N-CNT composite positive electrode active material according to claim 2, characterized in that: In step (2), the temperature of the calcination process is 500-750°C.

25. The method for preparing the sodium ferrous fluorophosphate / N-CNT composite positive electrode active material according to claim 24, characterized in that: The calcination time is 6~12h.

26. A use of the sodium ferrous fluorophosphate / N-CNT composite positive electrode active material according to claim 1, or the sodium ferrous fluorophosphate / N-CNT composite positive electrode active material prepared by any one of the preparation methods of claims 2 to 25, characterized in that: It is used to prepare sodium ion batteries.

27. The use according to claim 26, characterized in that It is used as a positive electrode active material to prepare the positive electrode of a sodium ion battery.

28. A sodium ion battery, characterized in that: The invention comprises the sodium ferrous fluorophosphate / N-CNT composite positive electrode active material as described in claim 1, or the sodium ferrous fluorophosphate / N-CNT composite positive electrode active material prepared by any one of the preparation methods of claims 2 to 25.

29. The sodium ion battery according to claim 28, characterized in that The positive electrode contains the sodium ferrous fluorophosphate / N-CNT composite positive electrode active material.

30. The sodium ion battery according to claim 29, characterized in that The positive electrode material contains the sodium ferrous fluorophosphate / N-CNT composite positive electrode active material.